EFEKTIVITAS MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA PRESENTASI PADA MATERI GERAK PARABOLA - Nofrince Pangumbahas; Jeane Verra Tumangkeng; Djeli Alvi Tulandi (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
This study aims to determine the effectiveness of the Project Based Learning (PjBL) model assisted by presentation media on physics material, namely parabolic motion in class X students at SMA Negeri 2 Tondano. The research method used in this study was a pre-experimental study with a One Group Pretest-Posttest design. The sample in this study was class XA students, totaling 27 students. Research data were collected using test instruments in the form of essay questions, project assessment observation sheets and attitude assessment using rubrics. Based on the results of data processing, it shows that the average posttest result of students is 85.30 which is classified as higher than the average student pretest result of 40.15. The results of the assessment of students' skills and attitudes during the learning process show results with an average score that is in the very good category. From the results of the N-Gain test, a gain score of 0.7579 was obtained, which showed that there was an increase in student learning outcomes in the moderate category with a percentage of 75.79% which was in the effective category. Based on these data, it can be concluded that the Project Based Learning model assisted by presentation media is effectively applied to parabolic motion material.